Representation of Masculine Woman in The Invitation (2022) - Dwiki Arif Nabil Mahbuby Mahbuby; Pita Merdeka (Universitas Muhammadiyah Surakarta, 2026)
This research discusses the representation of masculine women in the film The Invitation, using Roland Barthes' semiotic theory. This research aims to investigate how the representation of female masculinity is portrayed in the film The Invitation through the meaning of denotation, connotation, and myth. Then, several concepts related to the research, such as gender studies, masculinity, woman, masculine woman, and semiotics, are used. This research uses a qualitative method supported by semiotic and descriptive qualitative research. The data collection techniques for this research include observation, literature review, and additional sources. The result of the research is the traits and attitudes of masculine women depicted through Evie's character. The masculine traits and attitudes such as daring to take risks, resilience, assertiveness, and responsibility are shown in Evie's character. In conclusion, Evie's character exemplifies a dominant, masculine female who challenges stereotypical myths. Therefore, possessing masculine traits is entirely acceptable for women. Film is a powerful medium that can highlight the representation of women overcoming adversity and challenging prevailing stereotypes. It further represents women's vital roles within both personal and societal contexts.